Crise en Espagne et crise espagnole - Benoît Pellistrandi (Cahiers de Civilisation Espagnole Contemporaine)
The global recession that started in 2008 has been specific in Spain. In that country, in many ways, the crisis –which has been particularly serious– isn’t just economic but also political and has been accompanied by a loss of confidence in the validity of the “Spanish system” established in 1978.